Efficacy of prophylactic intravenous ondansetron for attenuation of pain on propofol injection - Manandhar, Sujita; Manandhar, Kishor (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Propofol is a popular intravenous anesthetic agent. One disadvantage of propofol is pain on its injection which can be excruciating at times. Various agents and methods have been tried to attenuate this unpleasant effect. Ondansetron, primarily used as an antiemetic has also been studied to reduce it. Methods: This randomized, prospective, double-blinded, placebo-controlled study was conducted on patients of either sex, American Society of Anesthesiologists (ASA) physical status I & II, undergoing elective surgeries requiring general anesthesia. The patients were randomly divided into ondansetron (A, received intravenous ondansetron 4 mg) and placebo (B, received equivalent volume of normal saline) groups. Manual occlusion of venous drainage was done at mid-arm by an assistant for 1 minute after which 25% of the calculated dose (2 mg/kg) of propofol (1% w/v in lipid base) was injected. Patients were asked by a blinded investigator to score the pain on injection of propofol on 4-point scale: 0=no pain, 1=mild pain, 2=moderate pain, 3=severe pain and compared in between two groups. The p<0.05 was considered significant. Results: There were 96 adult patients, 48 in each group of Ondansetron placebo. Pain on propofol injection was found significantly higher in the placebo group compared to the ondansetron group. (62.5% vs 35.4%). Most of the patients in the ondansetron group had mild pain only, whereas, a significant number of patients in the placebo group had higher degrees of pain on propofol injection. Conclusions: Prophylactic intravenous 4 mg ondansetron is a safe and simple method of attenuating pain on propofol injection.